2011
DOI: 10.1163/156854011x605765
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Recruitment of the Atlantic Seabob Shrimp, Xiphopenaeus kroyeri (Heller, 1862) (Decapoda, Penaeidae), on the Coast of Rio De Janeiro, Southeastern Brazil

Abstract: The objective of this study was to analyse the population growth of the Atlantic seabob shrimp, Xiphopenaeus kroyeri (Heller, 1862) and to establish its recruitment period in the northern part of the State of Rio de Janeiro, southeastern Brazil. Monthly samples of the species were collected over four years (2005-06, 2006-07, 2008-09, and 2009-10) through local artisanal fishery. The size of males and females varied from 25.0 to 134.0 mm and 33.0 to 146.0 mm in total length, 6.0 to 30.0 mm and 5.0 to 33.0 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…This reproductive dynamic agrees remarkably well with that reported for other populations of X. kroyeri in the northeastern, southeastern and southern regions of the Brazilian coast (e.g. Coelho & Santos 1993, Nakagaki & Negreiros-Fransozo 1998, Branco 2005, Castro et al 2005, Fernandes et al 2011 Table 3). Interestingly, this similarity in reproductive schedules among populations supports the notion that continuous reproduction with dissimilar intensity (i.e.…”
Section: Factors Correlating With Reproduction and Recruitmentsupporting
confidence: 90%
See 3 more Smart Citations
“…This reproductive dynamic agrees remarkably well with that reported for other populations of X. kroyeri in the northeastern, southeastern and southern regions of the Brazilian coast (e.g. Coelho & Santos 1993, Nakagaki & Negreiros-Fransozo 1998, Branco 2005, Castro et al 2005, Fernandes et al 2011 Table 3). Interestingly, this similarity in reproductive schedules among populations supports the notion that continuous reproduction with dissimilar intensity (i.e.…”
Section: Factors Correlating With Reproduction and Recruitmentsupporting
confidence: 90%
“…We have reviewed previous studies reporting CL 50 in X. kroyeri along the Brazilian coast and found considerable variability in this reproductive parameter (e.g. Coelho & Santos 1993, Branco et al 1999, Branco 2005, Fernandes et al 2011 Table 3). Our estimates of CL 50 are similar to those reported by G. S. Heckler et al (unpubl.)…”
Section: Size At First Maturitymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in South and Southeast of Brazil (Branco 2005, Castro et al 2005, Campos et al 2009, Fernandes et al 2011, Heckler et al 2013 showed that the juvenile recruitment of this species occurred close to the costal line, up to 15 m of depth, as we observed in the present study. We can infer that X. kroyeri in the Santos and São Vicente regions, as well as in the South and Southeast coast of Brazil, completes its life cycle at the in-shore areas and is not dependent on estuarine regions, and should be in life cycle type 3, according to the life cycle classification system of Dall et al (1990).…”
Section: Discussionsupporting
confidence: 85%